Impacts of Industrialization on Plant Species Composition, Diversity, and Tree Population Structure in Tropical Moist Deciduous Forest in Bangladesh - Nasima Akther Roshni; Mohammad Kamrul Hasan; Rojina Akter; A. K. M. Azad-Ud-Doula Prodhan; Ashaduzzaman Sagar (International Journal of Forestry Research)
Industrial activities have various effects on biodiversity, posing significant threats to forest ecosystems. The current study describes the species composition, taxonomic diversity, and stand structure at Bhawal Sal forest, Gazipur, Bangladesh, as they are affected by industrialization. To achieve the goal, 30 different categorized industries within the forest were considered sampling points and three distance gradient sites viz. Site-1 = Adjacent to industries (0 m), Site-2 = 160 m distance and Site-3 = 320 m distance from industries were designated as treatments. A total of 90 quadrate plots (10 m × 10 m) were taken randomly, of which 30 plots were from each site. Through forest inventory, 46 species (24 trees, 8 shrubs, 5 climbers, and 9 saplings) were recorded from three sites. The study revealed that the stand density and basal area of mature trees (257 stems ha−1 and 8.06 ± 0.60 m2·ha−1) at Site-1 were significantly lower due to diverse industrial operations than other sites. Statistically, all the biodiversity indices of mature trees; Shannon–Wiener’s index (1.72), Simpsons index (0.82), Margalef’s index (1.38), Pielou’s evenness Index (0.39) was found to be lower at proximity to industries. The lowest species richness (12) of all plants was recorded from Site-1. However, the diameter and height distributions of Site-1 comprised young (10–20 cm·dbh) to medium-sized (20.1–30 cm·dbh) trees, while the medium to large sized (>30 cm·dbh) trees was contained at Site-3 in this study. The population structure of tree species at Site-1 also showed a fluctuating curve. Overall, this study highlights that plant ecosystems and tree population structure have declined tremendously due to industrialization. Hence, the current research could be significant for developing the management framework for the disturbed deciduous forest.